An Ion‐Responsive Pincer‐Crown Ether Catalyst System for Rapid and Switchable Olefin Isomerization. (12th April 2017) - Kita, Matthew R.; Miller, Alexander J. M.
Abstract: Rapid, selective, and highly controllable iridium‐catalyzed allylbenzene isomerization is described, enabled by tunable hemilability based on alkali metal cation binding with a macrocyclic "pincer‐crown ether" ligand. An inactive chloride‐ligated complex can be activated by halide abstraction with sodium salts, with the resulting catalyst [ κ 5 ‐( 15c5 NCOP i Pr )Ir(H)] + exhibiting modest activity. Addition of Li + provides a further boost in activity, with up to 1000‐fold rate enhancement. Ethers and chloride salts dampen or turn off reactivity, leading to three distinct catalyst states with activity spanning several orders of magnitude. Mechanistic studies suggest that the large rate enhancement and high degree of tunability stem from control over substrate binding.